Becoming a Better Intern: The Fundamentals of Radiology in Internal Medicine - Adam Schwertner; Christopher Straus (Association of American Medical Colleges, 2014)
Abstract The following learning module focuses on the basics of radiology for the internal medicine specialty, and is constructed for fourth-year medical students and soon to be PGY-1 interns. The content within this module was identified by nonradiology internal medicine program directors to identify skills and knowledge needed to excel as an intern. Components of this resource include: (1) keywords and frequent vocabulary used in radiology reports, (2) fundamentals of image interpretation, and (3) radiologic exam selections with clinical scenarios. These three skills highlight the interplay between radiology and ordering physicians, which is vital to high-level patient care. All materials are included in an interactive PowerPoint presentation that requires the student to think about questions and find abnormalities on images before the answer is provided and explained. This module contains 35 common cases seen by an intern in internal medicine. Preliminary utilization by non-radiologist has been very favorable. Measurement of effectiveness through surveys is ongoing.